2022
DOI: 10.3389/fimmu.2022.918896
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, Effectiveness, and Safety of Inactivated Virus (CoronaVac) Vaccine in a Two-Dose Primary Protocol and BNT162b2 Heterologous Booster in Brazil (Immunita-001): A One Year Period Follow Up Phase 4 Study

Abstract: BackgroundEffective and safe vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are critical to controlling the COVID-19 pandemic and will remain the most important tool in limiting the spread of the virus long after the pandemic is over.MethodsWe bring pioneering contributions on the maintenance of the immune response over a year on a real-life basis study in 1,587 individuals (18-90 yrs, median 39 yrs; 1,208 female/379 male) who underwent vaccination with two doses of CoronaVac and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Therefore, the development of COVID-19 vaccines has been accelerated to prevent the spread of the virus and reduce the risk of severe illness. CoronaVac is the most widely utilized COVID-19 vaccine in China and has been introduced globally in more than 20 low-income and middle-income countries, such as Brazil, Chile, and Turkey (5)(6)(7). Studies showed that a two-dose CoronaVac regimen was effective in terms of an overall 67.7% (95% Confidence interval (CI), 35.9% to 83.7%) efficacy for the prevention of symptomatic COVID-19 and a 92% positivity of neutralizing antibodies (nAbs) among healthy adults (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of COVID-19 vaccines has been accelerated to prevent the spread of the virus and reduce the risk of severe illness. CoronaVac is the most widely utilized COVID-19 vaccine in China and has been introduced globally in more than 20 low-income and middle-income countries, such as Brazil, Chile, and Turkey (5)(6)(7). Studies showed that a two-dose CoronaVac regimen was effective in terms of an overall 67.7% (95% Confidence interval (CI), 35.9% to 83.7%) efficacy for the prevention of symptomatic COVID-19 and a 92% positivity of neutralizing antibodies (nAbs) among healthy adults (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In general, inactivated vaccines are associated with higher safety levels and mild adverse events when compared to attenuated virus and viral vector vaccines ( Murdin et al., 1996 ; Vellozzi et al., 2009 ; Xia et al., 2020 ; Ghattas et al., 2021 ). Additionally, when compared to mRNA, viral vector and subunit vaccines, known to induce the immune system using only a part of the virion, the use of a completely inactivated virus, with many viral epitopes, could allow the induction of a broad-spectrum immune response, with a wider efficacy range when compared to the other platforms, probably providing a greater range of protection against the first emerging variants of concern (Alpha, Gamma and Delta) ( Can et al., 2022 ; Cerqueira-Silva et al., 2022 ; Grenfell et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although longterm follow-ups remain unavailable, results from our study indicate low rates (0.3-0.6%) of breast discomfort following vaccination. Besides, axillary lymphadenopathy, which could be a clinical manifestation of ipsilateral breast cancer progression, was more commonly reported in cases who received mRNA vaccines (0.1-16%) (35), and most inactivated virus vaccines did not document axillary lymphadenopathy as a solicited adverse event (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%